FEATURES OF PSYCHOEMOTIONAL DISORDERS IN PREGNANT WOMEN AND WOMEN IN LABOR AGAINST THE BACKGROUND OF COVID-19 INFECTION (Conferencea, 2022)
To study the nature of psychosomatic disorders in pregnant women against the background of COVID-19 pneumonia.